2015
DOI: 10.7314/apjcp.2015.16.5.2037
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Platelet to Lymphocyte Ratio in the Diagnosis of Ovarian Neoplasms in Adolescents

Abstract: Background: Relationships between poor prognosis of ovarian malignancies and changes in complete blood count parameters have been proposed previously. In this work, we aimed to evaluate clinicopathologic features in adolescents with adnexal masses and sought to establish any predictive value of the platelet to lymphocyte ratio (PLR) in diagnosis. Materials and Methods: This retrospective study was conducted on 196 adolescent females with adnexal masses. Three groups were constituted with respect to clinical or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
4
25
1
Order By: Relevance
“…In healthy individuals, MPV and PDW values are counterbalancing each other. But previous studies of the MPV and PDW showed that this collateral distribution could change in various types of cancer (Okuturlar et al, 2015;Ozaksit et al, 2015). For example, a study of lung cancer patients reported that the MPV was lower and that the PDW was higher (Oncel et al, 2015), similarly to that what was found in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…In healthy individuals, MPV and PDW values are counterbalancing each other. But previous studies of the MPV and PDW showed that this collateral distribution could change in various types of cancer (Okuturlar et al, 2015;Ozaksit et al, 2015). For example, a study of lung cancer patients reported that the MPV was lower and that the PDW was higher (Oncel et al, 2015), similarly to that what was found in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…When PLR was compared with the other blood components, such as platelet count and NLR, PLR was found to be a better prognostic marker. In addition, PLR and poor survival of patients with advanced disease are markedly correlated (9,22,25). A possible limitation to this study is that we could not compare parameters according to histological subtypes in benign and malignant masses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predictive value of PLR in the diagnosis of ovarian neoplasms has been studied. In these studies, an increased PLR was found to be correlated with poor prognosis and decreased survival (9,10,22). In studies to identify alternative markers, a comparison between PLR and CA-125 revealed that a significant increase in PLR was correlated with CA-125 levels (p<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies comprising 1054 patients reported the PLR in patients with malignant ovarian masses and the controls [20][21][22][23][24][25] .…”
Section: Numerical Differences In Plr Between Patients With Malignantmentioning
confidence: 99%
“…The NOS scores, which indicated the quality of these studies, ranged from 6 to 8. Five of the selected eligible studies presented data regarding the association between the PLR and OS [14][15][16][17][18] , five studies discussed the link between PLR and PFS [15][16][17][18][19] , and six examined numerical differences in PLR between patients with malignant ovarian masses and the controls [20][21][22][23][24][25] . The disease characteristics in 12 studies are summarized in Table 2.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%